Fuzzy Logic: A Review - Hemba, S; Islam, N (International Journal of Computer Sciences and Engineering, 2025)
This paper discusses the Fuzzy logic concept based on the fuzzy set theory. Here, Fuzzy logic is discussed as a mathematical theory for the representation of uncertainty. This paper also contains a design outlook for fuzzy controller design.